A comparison of statistical methods for animal oncology studies. (31st August 2022) - Zhang, Tianhui; Novick, Steven J.
Abstract: In pre‐clinical oncology studies, tumor‐bearing animals are treated and observed over a period of time in order to measure and compare the efficacy of one or more cancer‐intervention therapies along with a placebo/standard of care group. A data analysis is typically carried out by modeling and comparing tumor volumes, functions of tumor volumes, or survival. Data analysis on tumor volumes is complicated because animals under observation may be euthanized prior to the end of the study for one or more reasons, such as when an animal's tumor volume exceeds an upper threshold. In such a case, the tumor volume is missing not‐at‐random for the time remaining in the study. To work around the non‐random missingness issue, several statistical methods have been proposed in the literature, including the rate of change in log tumor volume and partial area under the curve. In this work, an examination and comparison of the test size and statistical power of these and other popular methods for the analysis of tumor volume data is performed through realistic Monte Carlo computer simulations. The performance, advantages, and drawbacks of popular statistical methods for animal oncology studies are reported. The recommended methods are applied to a real data set.